Analisa Evaluasi Intensitas Konsumsi Energi Melalui Audit Energi Listrik Di Gedung Rektorat Universitas Riau - Bernadiktus, Fery; Hamzah, Amir (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The rapid growth of electricity needs were not followed by an increase in the supply of electric energy will trigger the electricity crisis. One effort that can be done to overcome the problem is to conserve energy. Energy conservation can be done through energy audits of electrical activity in the Rector Building , University of Riau . From the calculations, the intensity of the electrical energy consumption of the Rector Building , University of Riau for non - AC room of 4.93 kWh / m2 / month included in the criteria is very inefficient and 10.53 kWh / m2 / month for a room with air conditioning included in kriterian efficient . Based on research that has been made known that most of the room at the Rector Building , University of Riau has room temperature and lighting intensity below the standard value . Energy efficiency in the Rector Building Riau University can be improved by using energy-saving lamps , air conditioning maintenance routine and also implement energy-saving culture at the University of RiauKeywords: The intensity of energy consumption , Energy Audit , Energy Conservation